2013
DOI: 10.1088/0067-0049/210/1/4
|View full text |Cite
|
Sign up to set email alerts
|

The Next Generation Virgo Cluster Survey-Infrared (Ngvs-Ir). I. A New Near-Ultraviolet, Optical, and Near-Infrared Globular Cluster Selection Tool

Abstract: The NGVS-IR project (Next Generation Virgo Survey -Infrared) is a contiguous near-infrared imaging survey of the Virgo cluster of galaxies. It complements the optical wide-field survey of Virgo (NGVS). The current state of NGVS-IR consists of K s -band imaging of 4 deg 2 centered on M87, and J and K s -band imaging of ∼ 16 deg 2 covering the region between M49 and M87. In this paper, we present the observations of the central 4 deg 2 centered on Virgo's core region. The data were acquired with WIRCam on the Ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 75 publications
3
69
0
Order By: Relevance
“…The strongest gradients are found for u * -g within bright galaxies, inside 2.0 R e,g , while galaxies with M g > -15 have little-to-none in either color. Mild negative 4 UV and deep NIR imaging of the Virgo cluster exist (Boselli et al 2011;Muñoz et al 2014) but can only aid us for brighter galaxies and select fields, respectively. .…”
Section: The Red Sequence In the Core Of Virgomentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest gradients are found for u * -g within bright galaxies, inside 2.0 R e,g , while galaxies with M g > -15 have little-to-none in either color. Mild negative 4 UV and deep NIR imaging of the Virgo cluster exist (Boselli et al 2011;Muñoz et al 2014) but can only aid us for brighter galaxies and select fields, respectively. .…”
Section: The Red Sequence In the Core Of Virgomentioning
confidence: 99%
“…Briefly though, GCs and UCDs were both identified via magnitude cuts and the u * ıK diagram (Muñoz et al 2014), and separated from each other through size constraints [r h ≥ 11 pc for UCDs]. The validity of candidate GCs are assessed probabilistically and we use only those having a probability > 50%.…”
Section: Comparison To Compact Stellar Systemsmentioning
confidence: 99%
“…For example, H12 used this technique to discover 800 new GC candidates around NGC 5128 using B and R photometry. While this strategy is useful as a first guess, Muñoz et al (2014) recently showed the dramatically increased effectiveness of identifying GCs in colour-colour diagnostic space covering the NUV to near-infrared (NIR) SED range. Presently, there is no matching wide-field NIR photometry available for NGC 5128, so here we combine the u , r , and z filters from our survey which maximize the separation of GCs from background objects and, in particular, foreground stars.…”
Section: Two-colour Gc Selectionmentioning
confidence: 99%
“…Muñoz et al (2014) demonstrated that incorporation of K-band photometry in color-color selections provides a much better discriminant between GCs and contaminants. There are still difficulties with identifying real GCs outside typical color-color selections.…”
Section: Ground-based Photometry and Spectroscopymentioning
confidence: 99%